2019
DOI: 10.1590/1678-4499.20190114
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and toxic effects of selenium on seed germination of cowpea seedlings

Abstract: Selenium (Se) is considered a beneficial chemical element for plants, but in high concentrations it may present symptoms of toxicity. The present study aimed to evaluate 11 concentrations of Se (0; 0.1; 0.5; 1; 5; 10; 20; 40; 80; 400; 800 mg.L-1) to determine the low and high (toxicity) critical levels to seed germination of cowpea (Vigna unguiculata). In addition, alterations in the rate of photosynthetic pigments, lipid peroxidation and sugars during the initial growth development of seedlings were analysed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 41 publications
4
12
1
1
Order By: Relevance
“…However, other studies reported that the application of Se in low concentration causes positive effects on yield, biomass production, among other (Zhu et al, 2017). In contrast, high doses of Se cause toxicity in the plants because there is a high production of reactive oxygen species, found to inhibit growth and performance (Lapaz et al, 2019). The studies previously reported support our results that there is a decrease in grape production with higher concentrations of Se.…”
Section: Acumulación De Selenio En Los Frutossupporting
confidence: 89%
See 1 more Smart Citation
“…However, other studies reported that the application of Se in low concentration causes positive effects on yield, biomass production, among other (Zhu et al, 2017). In contrast, high doses of Se cause toxicity in the plants because there is a high production of reactive oxygen species, found to inhibit growth and performance (Lapaz et al, 2019). The studies previously reported support our results that there is a decrease in grape production with higher concentrations of Se.…”
Section: Acumulación De Selenio En Los Frutossupporting
confidence: 89%
“…Phenols concentration in grape fruits increased as doses of sodium producción de biomasa, entre otros (Zhu et al, 2017). Por el contrario, altas dosis de Se causan toxicidad en las plantas ya que existe una alta producción de especies reactivas de oxígeno, que se han descubierto que inhiben el crecimiento y el rendimiento (Lapaz et al, 2019). Los estudios previamente reportados apoyan nuestros resultados sobre que existe una disminución en la producción de uva con mayores concentraciones de Se.…”
Section: Total Phenolic Flavonoids and Antioxidant Capacityunclassified
“…The lower content of chlorophylls and carotenoids impairs the use and dissipation of light energy, which can result in reduced photosynthesis (Divya et al 2018;Lapaz et al 2019). Therefore, reduction in chlorophyll content may have contributed to the lower A observed in this study (Table 1 and Fig.…”
Section: Photosynthetic Pigmentsmentioning
confidence: 76%
“…The decrease in chlorophyll and carotenoid contents when HLB-infected plants were treated with the application of SeNPs at a concentration of 100 mg L −1 might be due to many reasons, such as the generation of ROS, which cause oxidative damage to the plant. It has also been reported that high amounts of selenium interface with amino acids having selenium and sulfur metabolisms and displace sulfur amino acids and proteins synthesized by them, which alter plants’ physiological and biochemical profiling [ 67 ].…”
Section: Discussionmentioning
confidence: 99%